Walt Whitman speaks his final thoughts on life, writing, spirituality, and the promise of America, as told to Horace Traubel ; edited and with an introduction by Brenda Wineapple - Whitman, Walt 1819-1892; Traubel, Horace 1858-1919 (Library of America, 2019)
"Here is Whitman the sage, champion of expansiveness and human freedom. Here too, is the poet's more personal side--his vivid memories of Thoreau, Emerson, and Lincoln, his literary judgments of writers such as Shakespeare, Goethe, and Tolstoy, and his expressions of hope in the democratic promise of the nation he loved. The result is a keepsake edition to touch the soul, capturing the distilled wisdom of America's greatest poet"--from Jacket
Keywords: Whitman, Walt / 1819-1892 / Interviews; Whitman, Walt / 1819-1892 / Anecdotes; Whitman, Walt / 1819-1892; Traubel, Horace -- 1858-1919; Whitman, Walt -- 1819-1892; Geschichte 1888-1892; Poets, American / 19th century / Interviews; Poets, American